Effect of professional events on competences for encouraging reading literacy - Vilar, Polona; Fras Popović, Sabina (Vjesnik bibliotekara Hrvatske, 2022)
Purpose: We want to determine the impact of participation in a professional event on the competences of library professionals in the field of reading literacy. We are interested to find whether professionals are more motivated to work after attending a professional event, feel more confident in working in the field of reading literacy, more connected to others and see more sense in their work, and whether participation in the event affects their work activities after the event itself. Methodology: We used a case study with a quantitative survey method to collect data. First, we analysed selected scientific and professional literature to define the concepts of motivation, self-confidence, belonging and meaning, and responsibility of an individual‘s professional development. We linked our case study to the predefined theoretical starting points. The design of the questionnaire structure was linked to the impact assessment. Results: Understanding the concepts of motivation, self-confidence, belonging and meaning is crucial in strengthening the competences of professional staff. In the first part we compare the results over a three-year period, and in the second part we use the results to determine how participation in a professional event affects the individual. Comparative results of all three events show that obtaining the necessary information positively affects self-confidence at work. The research has shown that participation in a professional event has a positive effect on motivation, belonging, meaningful work and understanding of professional and personal role. Research limitations are linked to the size of the study, as it is based on one case study, but includes a large enough sample that can indicate the starting point for a more extensive study to determine the impact of professional events on motivation, confidence, belonging and acceptance meaningful in the professional field. Originality/value: Studies of the impact of participation in professional trainings on the competences of professionals are rare, so our research is an additional incentive to argue for regular professional training and monitor the development of individual key elements (i.e. motivation, confidence, meaning, belonging) of professional competencies. The research highlights the importance of an individual‘s commitment to promoting reading literacy and building reading culture.